Syntax and its limits - Folli, Raffaella; Sevdali, Christina; Truswell, Robert (Oxford studies in theoretical linguistics, 2013)
In this book, leading linguists explore the empirical scope of syntactic theory, by concentrating on a set of phenomena for which both syntactic and nonsyntactic analyses appear plausible. The volume is organized into four thematic sections: architectures; syntax and information structure; syntax and the lexicon; and lexical items at the interfaces.